Learning Obstacles of Bachelor of Science in Office Administration Students in Shorthand - Bufete, Jonalie T.; Moreno, Maria Theresa A.; Mejaro, Mark Kenneth G.; Marpuri, Jessica C. (The Indonesian Institute of Science and Technology Research, 2025)
This study explores the learning challenges faced by Bachelor of Science in Office Administration (BSOA) students at Camarines Sur Polytechnic Colleges in mastering shorthand—a vital skill for efficient transcription in professional settings. Guided by the Skill Acquisition Theory of Fitts and Posner (1967), the research focuses on identifying difficulties in dictation and transcription and suggests ways to improve student proficiency. Despite technological advancements, shorthand remains relevant, though students often struggle due to limited practice and inadequate instructional support. Using a descriptive approach, the researchers surveyed 187 second-year BSOA students through questionnaires, with data analyzed using weighted mean and percentage techniques. Results show that while students demonstrate strong skills in dictation and transcription, they still encounter key challenges. These include difficulty with unfamiliar words, lack of focus during dictation, and poor penmanship leading to inaccurate strokes. These obstacles hinder mastery of shorthand. The study concludes that these issues are primarily due to insufficient exposure and practice. To address this, the researchers recommend implementing specialized training programs, incorporating real-life scenarios in instruction, organizing student focus groups, and conducting frequent assessments to monitor progress.